Study of Micellar Behavior of a Tween 80 Surfactant in Aqueous Media Containing Diphenhydramine Hydrochloride - Azeez, Maryam A.; Ali, Inaam H.; Kareem, Sameer H. (Iraqi Journal of Science, 2022)
The surface properties of mixtures of a nonionic surfactant Tween 80 (Tw 80) and a cationic drug, diphenhydramine HCl (DPH) have been investigated. This was done by calculating the surface excess concentration (Γmax), minimum molecular area (Amin), surface pressure at the CMC (ᴨcmc), Gibbs Free Energy of adsorption (ΔG°ads), Gibbs free energy of micellization (ΔG°m), the standard enthalpy of micellization (ΔH°m), and the standard entropy of micellization (ΔS°m). The calculation was performed using the surface tension in the temperature range of 293-323 K with the variation of surfactant concentration to determine the critical micelle concentration (cmc) of the system studied. The variation of cmc values of drug concentration (DPH) with temperature was used to calculate the parameters above. The results indicate that the cmc values of Tw 80 increased when the (DPH) was added and when the temperature increased at the whole temperature studied. The results obtained for interfacial properties show that Γmax decreases with the addition of DPH and decreases with DPH concentration increase from 10-5 to 10-4M and decreases with temperature increases. The results of thermodynamic properties indicate that the micellization and adsorption at the interface are spontaneous and the ΔG̊ads are more negative than ΔG̊m at all temperatures.